PERSENTASE KEJADIAN KAWIN BERULANG SAPI PERAH YANG TELAH DI IB (INSEMINASI BUATAN) TINGKAT PETERNAK DESA NYAWANG KIDUL DI KUD TANI WILIS KECAMATAN SENDANG KABUPATEN TULUNGAGUNG - Setyadi, Arda Wahyu; Srianto, Pudji; Widodo, Oky Setyo; Wurlina, Wurlina; Samik, Abdul; Restiadi, Tjuk Imam (Ovozoa: Journal of Animal Reproduction, 2019)
Dairy cows farm business level of KUD Tani Wilis in Nyawang Kidul, Sendang district, Tulungagung city has some problems resulting low livestock productivity. One of the causes of low levels of dairy reproductivity is the incidence of repeat breeder. Repeat breeder is a condition of a female cow that failed to breed after being mated three or more times with a normal and healthy fertilized bull. The main purpose of this research is to know the risk factor of repeat breeder in dairy cows at farmer level of KUD Tani Wilis in nyawang kidul, Sendang district, Tulungagung city. The type of research is descriptive research. This research was using 32 dairy cows from 6 breeders, the selection of cattles used Simple Random Sampling method. The collection data using questionnaires and direct observations in farms resulted that the evidence rate of dairy cattle's repeat breeder in this research is 45.7%. The results also showed that the influence of knowledge of farmers on disease or reproductive disorders positively correlated with the evidence of repeat breader.